PENGARUH PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN MODERN TERHADAP KEPATUHAN WAJIB PAJAK - Rochmah, Alia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of implementation of modern taxation administration system which includes i.e.: the modernization of organization structure, modernization of organization procedure, modernization of organization strategy, and modernization of organization culture of to the taxpayersâ compliance. The type of research is descriptive research. The samples are determined based on Convenience Sampling method in which the collection of information from the membersâ population who are willing to give information and to get the basic information efficiently and rapidly, therefore 85 respondents of taxpayer at KPP Pratama Surabaya Wonocolo have been selected. The primary data is used in this research. The survey method is used as the data collection technique. The data is obtained by distributing questionnaires. The multiple linear regressions model is used in this research.The result of the research shows that there is positive influence among the modernization of organization structure variable in the implementation of modern taxation administration system to the taxpayersâ compliance. Where as the others variables which include modernization of organization procedure, modernization of organization strategy, and modernization of organization culture have no influence to the taxpayersâ compliance.Keywords: The Implementation of Modern Taxation Administration System, the Modernization of Organization Structure, Taxpayersâ Compliance.